Highly active and inexpensive iron phosphide nanorods electrocatalyst towards hydrogen evolution reaction. (2nd November 2015) - Du, Hongfang; Gu, Shuang; Liu, Rongwei; Li, Chang Ming
Abstract: Herein for the first time we report a novel approach to prepare well-controlled iron phosphide nanorods (FeP NRs) via low-temperature phosphidation of Fe salt with a porous anodic aluminum oxide (AAO) template. The as prepared FeP NRs exhibit high catalytic activity toward hydrogen evolution reaction (HER) in acidic solutions, showing an onset potential of ∼45 mV, a Tafel slope of 55 mV/dec and nearly 100% Faradaic yield (FY) with good stability. Additionally, the catalyst can deliver current density of 2 and 10 mA/cm 2 for HER with low overpotentials of 67 and 120 mV, respectively. Up to date the FeP NRs should be the inexpensive electrocatalyst while offering high activity toward HER, thus holding a great promise for practical applications for water electrolysis in large scale production. Graphical abstract: Highlights: Novel FeP nanorods electrocatalyst was successfully synthesized via a hard template strategy. The FeP nanorods exhibit excellent activity towards hydrogen evolution reaction. The catalyst shows superior stability during operation in acid conditions.